Piperlongumine is a ligand for the orphan nuclear receptor 4A1 (NR4A1) - Zhang, Lei; Martin, Greg; Mohankumar, Kumaravel; Wright, Gus A.; Mariyam, Fuada; Safe, Stephen (Frontiers in Pharmacology, 2023)
Piperlongumine and derivatives are being developed as anticancer agents which act primarily as inducers of reactive oxygen species (ROS) in cancer cell lines. Many of the anticancer activities of piperlongumine resemble those observed for bis-indole derived compounds that bind the orphan nuclear receptor 4A1 (NR4A1) and act as inverse receptor agonists to inhibit NR4A1-regulated pro-oncogenic pathways and genes. In this study we show that like other NR4A1 inverse agonists piperlongumine inhibited RKO, SW480 and HCT116 colon cancer cell growth migration and invasion and induced apoptosis. Piperlongumine also downregulated the pro-reductant isocitrate dehydrogenase 1 (IDH1) and thioredoxin domain-containing 5 (TXNDC5) gene products resulting in the induction of ROS as previously observed for other inverse NR4A1 agonists. ROS also induced sestrin2 and this resulted in activation of AMPK phosphorylation and inhibition of mTOR pathway signaling. It has previously been reported that these pathways/genes are also regulated by inverse NR4A1 agonists or by knockdown of NR4A1. We also observed that piperlongumine directly bound NR4A1, inhibited NR4A1-dependent transactivation and interactions of the NR4A1/Sp1 complex bound to the GC-rich promoter of the NR4A1-regulated G9a gene.